An artificial light-harvesting system with sequential energy transfer for information dual encryption and anticounterfeiting. Issue 34 (12th August 2022) - Xia, Yan; Chen, Maowen; Li, Suwan; Li, Man; Li, Xianying; Yi, Tao; Zhang, Dengqing
Abstract : The artificial light-harvesting system (MPy1 –ESY–SR101) with two-step sequential energy transfer constructed in this work serves as a privileged platform for multilevel data encryption and anticounterfeiting. Abstract : Multilevel information encryption and anticounterfeiting are extremely important for information security. Herein, we employed a hexagonal pyrene-based organoplatinum (II) metallacycle (MPy1 ) as a platform to construct an artificial light-harvesting system with two-step sequential energy transfer and eosin Y serving as a bridge between the initial energy donor (MPy1 self-assembly) and final energy acceptor (sulforhodamine 101). The artificial light-harvesting system (MPy1 –ESY–SR101) showed promising application in multilevel data encryption and anticounterfeiting. The dual-encryption QR (quick response) code can only be readable under 365 nm UV light and the THF vapor environment. The protected information is very difficult to be copied and counterfeited because the emission spectra of the MPy1 –ESY–SR101 system depend nonlinearly on the ratio of the energy donor and two acceptors.